Pertimbangan Hukum Mahkamah Agung terhadap Error in Judicio pada Perkara Narkotika (Studi Kasus Putusan Nomor 2415 K/Pid.Sus/2015) - Elsa Alva Anindya; Zerry Akbar Yudisetyo (CV Rewang Rencang, 2025)
This study examines the misapplication of evidentiary law by the judicial reviewer (judex facti) in narcotics cases, as exemplified by Supreme Court Decision No. 2415 K/Pid.Sus/2015. This example demonstrates the error in judicio. The first-instance and appellate judges misjudged the facts, misinterpreted the elements of the offense, and misassessed the evidence, resulting in the decision failing to meet the evidentiary standard under Article 184 of the Criminal Procedure Code and violating the defendant's rights. The Supreme Court corrected this error through an appeal and emphasized the importance of applying the correct evidentiary standard. The study concludes that this error impacts the quality of decisions and legal certainty, necessitating improvements in judicial competence and clearer evidentiary guidelines in narcotics cases.